Teacher Professional Development for the Integration of Content and Language in Higher Education, edited by Mª Noelia Ruiz-Madrid and Inmaculada Fortanet-Gómez (Routledge, 2024) - Gonzalez, Flor (Miscelánea: A Journal of English and American Studies, 2025)
The rise of content subjects taught in English as an additional language is one of the most significant phenomena concerning language in contemporary higher education (Macaro et al. 2018). The implementation and teaching of Integrated Content and Language in Higher Education (ICLHE) or English as Medium of Instruction (EMI) entails myriad interrelated factors that pivot on student-centred learning, from learners’ language and subject learning needs to the design of context and language-specific materials. For this reason, training lecturers on how to teach learners in an additional language in Higher Education remains a challenge for the profession. The most recent publications extolling that support courses focus on language and teaching methodology in a much more integrated manner (Dimova et al. 2023; Lasagabaster 2022). Mª Noelia Ruiz-Madrid and Inmaculada Fortanet-Gómez’s book responds to this call by providing a compilation of the innovative work of different researchers in Europe (Austria, Finland, Italy and Spain) on how universities, researchers and practitioners are facing and developing ICLHE teacher training. These contributions shed new light on a range of issues that play a fundamental role in the design of effective ICLHE professional development. Every chapter furnishing novel data, reflections and implications that serve to inform future ICLHE teacher training programmes. The main objective, to elucidate upon the key factors that afford a learner-centred interactive approach to the design of effective ICLHE teacher training proposals. Resources in the volume will be of interest to academics, researchers, and advanced students of Education and Teacher Training Research and Practice.